Microeconomics - Robert S Pindyck; Rubinfeld,Daniel L; Banerjee,Sreejata (Chennai Pearson, 2024)
Microeconomics, 9e provides an exciting and dynamic approach to how microeconomics can help us to understand what goes on in the world and how it can be used as a practical tool for decision making. To facilitate classroom learning needs, this edition provides a treatment of microeconomic theory that stresses its relevance and application to both managerial and public policy decision making. This applied emphasis is accomplished by including examples that cover such topics as the analysis of demand, cost, and market efficiency the design of pricing strategies investment and production decisions and public policy analysis. The book also covers new topics that have come to play a central role in microeconomics over the years, such as game theory and competitive strategy, the roles of uncertainty and information, and the analysis of pricing by firms with market power. The coverage in the book is comprehensive and up-to-date as well as lively and engaging for students with a broad range of academic backgrounds.
Keywords: Microeconomics